Ultraprocessed food and chronic noncommunicable diseases: A systematic review and meta‐analysis of 43 observational studies. (9th November 2020) - Lane, Melissa M.; Davis, Jessica A.; Beattie, Sally; Gómez‐Donoso, Clara; Loughman, Amy; O'Neil, Adrienne; Jacka, Felice; Berk, Michael; Page, Richard; Marx, Wolfgang; Rocks, Tetyana
Summary: This systematic review and meta‐analysis investigated the association between consumption of ultraprocessed food and noncommunicable disease risk, morbidity and mortality. Forty‐three observational studies were included ( N = 891, 723): 21 cross‐sectional, 19 prospective, two case‐control and one conducted both a prospective and cross‐sectional analysis. Meta‐analysis demonstrated consumption of ultraprocessed food was associated with increased risk of overweight (odds ratio: 1.36; 95% confidence interval [CI], 1.23‐1.51; P < 0.001), obesity (odds ratio: 1.51; 95% CI, 1.34‐1.70; P < 0.001), abdominal obesity (odds ratio: 1.49; 95% CI, 1.34‐1.66; P < 0.0001), all‐cause mortality (hazard ratio: 1.28; 95% CI, 1.11‐1.48; P = 0.001), metabolic syndrome (odds ratio: 1.81; 95% CI, 1.12‐2.93; P = 0.015) and depression in adults (hazard ratio: 1.22; 95% CI, 1.16‐1.28, P < 0.001) as well as wheezing (odds ratio: 1.40; 95% CI, 1.27‐1.55; P < 0.001) but not asthma in adolescents (odds ratio: 1.20; 95% CI, 0.99‐1.46; P = 0.065). In addition, consumption of ultraprocessed food was associated with cardiometabolic diseases, frailty, irritable bowel syndrome, functional dyspepsia and cancer (breast and overall) in adults while also being associated with metabolic syndrome in adolescents and dyslipidaemia in children. Although links between ultraprocessed food consumption and some intermediate risk factors in adults were also highlighted, further studies are required to more clearly define associations in children and adolescents. Study registration: Prospero ID: CRD42020176752.